'Secondary biofilms' could cause failure of peracetic acid high-level disinfection of endoscopes. (January 2021) - Akinbobola, A.B.; Amaeze, N.J.; Mackay, W.G.; Ramage, G.; Williams, C.
SUMMARY: Introduction: The reduced susceptibility of biofilms to disinfectants presents a challenge to the successful reprocessing of medical equipment. This study examined the effect of residual biomass remaining after previous disinfection with peracetic acid (PAA) on the tolerance of subsequent mature Pseudomonas aeruginosa biofilms to PAA. The effect of enzymatic degradation of specific components of the extracellular polymeric substance (EPS) of P. aeruginosa biofilm on the effectiveness of PAA disinfection was also evaluated. Methods: The susceptibility of biofilm grown on the biomass of PAA-killed biofilm to PAA was compared with the PAA susceptibility of biofilm grown in wells of a 24-well plate by evaluating their viability using the plate count assay. The effect of PAA on biofilm biomass was measured using crystal violet quantification of total biofilm biomass, while its effect on the polysaccharide and protein components of biofilm EPS was quantified using the phenol-sulphuric acid assay or Bradford assay, respectively. A confocal microscope was used to visualize the distribution of living and dead cells in biofilms grown on residual biofilm biomass. Findings: The presence of residual biomass from previously disinfected biofilms significantly enhanced the tolerance of subsequent biofilms. A 96-h-old 'secondary biofilm' formed on disinfected biomass survived PAA concentrations of 4000 ppm, which exceeds the concentrations used in practice for high-level disinfection. Conclusion: These observations indicate that, under certain circumstances, recolonization of residual EPS can cause failure of disinfection of medical equipment such as endoscopes, and emphasizes the importance of cleaning endoscopes prior to disinfection.